Élaboration d’un protocole de suivi de la fréquentation au sein de la Réserve naturelle marine de la Réunion, France, Océan Indien - Anne Lemahieu; Gwenaëlle Pennober; Gilbert David; Franck Lavigne; Karine Pothin; Léa Gérard (VertigO)
The Natural Marine Reserve of La Reunion (RNMR) was established in 2007 along a weakened fringing reef which extends over forty kilometers along the western coast. These last decades, this latter was submitted to a rapid and dense urbanization, namely due to its attractive seaside assets. Simultaneously, increasing coastal activity and emergence of new practices put new issues forward, such as potential impacts on the environment, and potential conflicts that may occur. Besides, Marine Protected Areas (MPAs) effectiveness cannot longer be evaluated from biological markers only, and socio-economical parameters tend to be taken into account by high national bodies (French Agency for MPA) and managers during management plan development. From 2010, a vast French national campaign was launched to assess socio-economical needs in terms of markers, and to develop a common methodological framework for marine and coastal uses monitoring. Through this study, the RNMR equipped themselves with a methodological and operational framework for uses monitoring in order to develop and integrate markers to their management plans, permitting the measurement of management effectiveness. Between January and July 2010, 14 uses including swimming, beach going, water sports and fishing have been monitored using an ultra-light aircraft and a camera .48 flights were planned over this period according to a temporal stratification (Summer/Winter, Holidays/School days, week/weekend and morning/afternoon). Data were integrated to a Geographic Information Base offering a range of spatial analysis and statistics tools. Results show a heterogeneous users distribution in time and space which peaks can reach nearly 10,000 users. Half of users remains concentrated on a small portion of the coastline equivalent to 8% of the total coastal length of 44 kilometers and spread over four main sites (Boucan-Canot, Ermitage, La Saline and Etang-Salé) which correspond to the sites the most equipped with amenities (coral-free swimming areas, coral sand) and services (parks, bars, lifeguards). In addition, this uses’ monitoring protocol has many potentialities in terms of management and scientific accumulation of learning outcomes, which are set forth in discussion.